Luminescence properties and ROS generation of magnetic porous silicon nanoparticles - Caregnato, Paula (2020)
Magnetite‒Porous Silicon 100−150 nm size nanoparticles (MPSi) were obtained combining luminescent and magnetic properties from silicon and magnetite, respectively. MPSi hybrids were characterized by high-resolution transmission electron microscopy, atomic and magnetic force microscopy and X-ray photoelectron spectroscopy. The presence of magnetite quenches statically visible luminescence of Porous Silicon toluene suspensions. Whereas MPSi, maintain the luminescence in the 300−450 nm spectral region. Particles retained the capacity for singlet oxygen and superoxide radical ion generation (Reactive Oxygen Species, ROS). However quantum yield singlet oxygen generation is much lower than the PSi analogues and superoxide radical ion concentration dismiss when magnetite is incorporated in the PSi matrix. Silanization of Porous Silicon and MPSi yield nanoparticles with − SH terminal groups with unique luminescence properties.